Nine Years of Evolution of a Clinical Case of Avulsion of a Permanent Tooth (Update Dental College Journal, 2024)
Introduction: A clinical case involving a 13-year-old boy with dental avulsion of his right upper central incisor and a concurrent soft tissue lesion on the lip is presented. The initial treatment involved lip suturing and reimplantation of the avulsed tooth, followed by splinting and bonding for a specified duration.Methods: Following the initial treatment, a control x-ray at the six-month mark revealed a radiolucent image at the tooth apex, prompting a decision to proceed with root canal treatment. Subsequently, after a period of nine years, the reimplanted tooth exhibited shortening and darkening, though its function remained unaffected.Results: Despite the observed changes in tooth appearance over the nine-year period, the functionality of the reimplanted tooth was not compromised. The treatment approach involving reimplantation and subsequent root canal treatment proved effective in preserving dental function and aesthetics.Conclusion: The findings suggest that reimplantation of a permanent tooth following avulsion can serve as an effective long-term treatment strategy. This approach not only preserves dental function and aesthetics but also delays the potential need for implant or prosthesis placement. Therefore, it should be considered as the primary therapeutic option in cases of dental avulsion, emphasizing its role in achieving favorable long-term outcomes.Update Dent. Coll. j: 2024; 14(1):24-27